Cambodia : Can Transparency and Incentives for Community Participation Increase the Supply of Textbooks to Schools? - World Bank (World Bank, Washington, DC, 2020)
The textbook supply chain in Cambodia has several weak points. Book forecasting can take many months, as schools report their book needs to district or cluster officers who then collate all the requirements of the schools within their jurisdiction and report them to the national government. This process is also not well aligned with the government budgeting processes which further exacerbates delays. Schools fill out paper-based forms with complex formulae to determine the number of books the schools need, making the process prone to errors. The distribution of books is also a time-consuming process and prone to error. When the books are printed and dispatched, district or cluster officials receive a bulk allocation for all their schools and are then required to collate and repackage the books destined for each school, which introduces a risk of error. Then the school directors (or headteachers) collect their schools’ books from the district and report the receipt of the books using a complex paper receipt template, which is time-consuming to complete and also prone to error. As a result of these weaknesses in the supply chain new textbooks often do not reach schools on time or in the correct quantities. In the baseline for this study, only around 65 percent of school directors surveyed reported having adequate numbers of textbooks for key subjects, and 45 percent did not receive their books in time for the start of the school year. Consequently, it is estimated that more than 2 million primary school students in Cambodia face a chronic lack of good quality textbooks.